Influence of different caregiving styles on fundamental movement skills among children - Hu, Jiahui; Zhang, Shudan; Ye, Weibing; Zhu, Yuanye; Zhou, Huiling; Lu, Lihua; Chen, Qian; Korivi, Mallikarjuna (Frontiers in Public Health, 2023)
This study investigated the influence of parenting and grandparenting caregiving styles on fundamental motor skills (FMS) of preschool children. Method: A total of 1326 preschool children (698 boys, 628 girls) aged 4-6 years were recruited from the kindergartens of Jinhua City, China. Locomotor skills (LM), ball skills (BS) and total fundamental movement skills (TS) of children were assessed by the Test of Gross Motor Development-3 rd edition (TGMD-3). Results: There were 978 children in parenting and 348 children in grandparenting caregiving styles. The LM, BS and TS scores of children were considerably (p<0.001) increased with age (irrespective of sex or caregiving style). For the sex comparisons, BS scores of boys were significantly higher than girls (p<0.001), while LM and TS scores were not different between boys and girls. For the caregiving style comparison, parenting is superior to grandparenting in developing of children's FMS. Parenting boys of 4-, 5-and 6-years old showed better BS compared to age-matched parenting girls, whereas boys of 5-years old in grandparenting only showed better BS compared to same-age grandparenting girls (p<0.05). Furthermore, parenting boys of 6-years reported higher LM (p<0.01), BS (p<0.001) and TS (p<0.001) scores compared to grandparenting boys, but girls' FMS at all ages were not significantly different between the caregiving styles. Conclusion: Parenting caregiving style is positively associated with proper development of FMS among children. Improved FMS proficiency helps children to enhance their cognitive function, academic performance and physical fitness.